Blockchain Based Intellectual Property Management Enhancing Security and Transparency in Digital Entrepreneurship - Murod, Ma’mun; Anhar, Syafrudin; Andayani, Dwi; Fitriani, Anandha; Khanna, Gautam (Pandawan, 2025)
The protection and management of intellectual property (IP) have become increasingly complex in the digital era. Traditional methods face significant challenges due to the ease of digital content replication and distribution. This research aims to explore the potential of blockchain technology in addressing these challenges in IP management and copyright protection. A quantitative approach using SmartPLS analysis was conducted, surveying 100 respondents from companies in Indonesia. The results indicate that IP protection, the efficiency of IP management, and transparency are critical factors in driving the adoption of blockchain technology. These factors enhance the effectiveness of IP management systems by ensuring security, reducing administrative costs, and improving overall transparency. The study findings have important implica tions for decision-makers, providing valuable insights into how blockchain can be implemented to optimize IP protection and management processes. This research highlights the need for further development of blockchain-based solutions to support IP management, offering a more efficient, transparent, and secure framework. The adoption of blockchain in this context is essential to revolutionizing IP management practices in the digital age.